INTEGRATED SEISMIC HAZARD EVALUATION OF JAVA ISLAND BASED ON PEAK GROUND ACCELERATION AND HISTORICAL SEISMICITY - Tati Zera; Rindi Antika Sari; Talitha Adinda (Department of Physics, Faculty of Science and Technology, UIN Syarif Hidayatullah Jakarta, 2025)
Abstract. Java Island is characterized by intense seismic activity due to its position at the convergence of the Indo-Australian, Eurasian, and Pacific plates. This tectonic setting, compounded by the presence of active fault systems, renders the region highly vulnerable to destructive earthquakes. This study investigates seismic hazards over a fifty-year period (1974–2024), focusing on events with magnitudes greater than 5 and depths shallower than 60 km. Peak Ground Acceleration (PGA) was selected as the primary parameter, given its critical role in assessing potential structural damage. Three established models—Donovan, Esteva, and McGuirre—were applied, producing PGA values ranging from 0.0046–0.1573 g, 0.00019–0.0292 g, and 0.00682–0.2206 g, respectively. These results were subsequently converted into the Modified Mercalli Intensity (MMI) scale to provide a practical measure of seismic hazard. The highest PGA was linked to the M 6.6 earthquake of January 14, 2022. Findings underscore the necessity of empirically grounded mitigation strategies to enhance resilience and inform sustainable development across Java. Keywords: Donovan, Esteva, earthquake, McGuire method, peak ground acceleration